HUBUNGAN POLA DIET MAKANAN BERBASIS KEDELAI DENGAN KELUHAN GANGGUAN MENOPAUSE - Tiwi Yuniastuti; Ari Christina (Jurnal Ilmiah Kesehatan Media Husada, 2014)
Menopause is the process of cessation of menstruation permanently because of aging the ovary that is influential on secretions of estrogen, progesterone, and prostaglandins. Menopause result in condition vasomotor, cardiovascular, psychological and sexually will influence the quality of life woman. This condition necessary repairs through setting a diet of foods containing fitoestrogen an alternative as a substitute for estrogen natural. The purpose of this study is to see how the influence of soy-based food diet by female age group 51- 70 years against disturbances of menopause, especially disorders of cardiovascular disease by the method of Menopausal Rating Scale (MRS). This research using methods interview open observation lapangan kuisioner by method and menopausal rating scale. Data analyzed by employing correlation pearson through spss aid program. The results of data analysis of respondents indicated that there was no significant influence between consumption of especially food dna-based soybean with impaired complaint menopause. It is caused by the presence of factors of who also affecting, namely nutrition status, a disease that suffered and physical activity that is performed. The conclusion is consumption of especially food dna-based soybean only paid little influence against the minimization of disorder, complaints menopause because there were of factors of who participate in influence.